Spotlighting the trends in the inclusive education research in Nigeria - Lawal, Mary Oluwatosin (Вестник Томского государственного университета. Философия. Социология. Политология)
This article presents a systematic review of the scholarship in the area of inclusive education in Nigeria, highlighting current trends, challenges, and prospects. The analysis reveals a paucity of scholarly research pertaining to inclusive education within Nigeria as reflected in international academic journals. A specific gap that has been delineated is the predominant focus of existing studies on disability, with scant attention afforded to gender, socio-economic status, ethnicity, among other pertinent characteristics of exclusion.